A taxonomic study of the genus Isturgia from China (Lepidoptera, Geometridae, Ennominae) - Mi, Xiaoye; Cheng, Rui; Han, Hongxiang (Zootaxa, 2026)
The genus Isturgia Hübner, 1823 in China is reviewed. Ten species are recognized, of which, Isturgia bisinuata sp. nov. from Xizang is described as new to science. Two new combinations are established (Isturgia anostilpna (Wehrli, 1938) comb. nov., and Isturgia isogrammica (Wehrli, 1937) comb. nov.) and Isturgia murinaria is reported as a new record for China. Diagnoses for all species are provided, and illustrations of external features and genitalia are presented.